Peningkatan Kemampuan Pemecahan Masalah menggunakan Model Problem Based Learning Berbantuan Video Pembelajaran Di Sekolah Dasar - Hayati, Rahmi; Fachrurazi, Fachrurazi; Karim, Asrul; Marzuki, Marzuki (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
This research uses a quantitative approach. This study aims to determine the increase in problem-solving skills using the Problem-Based Learning Model, which is better than what is taught through conventional learning assisted by Video Learning in Elementary Schools. The type of research used in this research is experimental. Data collection techniques in this study were carried out through tests, namely pre-tests and post-tests, in the form of problem-solving ability tests and observations of the learning. The pre-test was carried out before the learning took place, and the post-test was carried out after the learning took place on both experimental and control groups. This instrument consists of test questions to measure students’ problem-solving abilities. Data were analyzed by comparing student scores obtained from student results before and after being treated with conventional learning. The study results concluded that the obtained t-table value could be written as follows; t-table with a significance level of 5% = 1.303 < t-count = 2.076 for t-count or ha is accepted and ho is rejected. This video-based PBL model is suitable for learning mathematics in elementary schools.